In vitro and in vivo approaches demonstrating the antiproliferative activity of pomegranate seed proteins and peptides on breast cancer - Miriam Guzmán-Lorite; Laura Muñoz-Moreno; María Luisa Marina; María José Carmena; María Concepción García (PLoS ONE, 2025)
Pomegranate seed proteins and peptides exhibit high antioxidant capacity according to previous work carried out by our group. The present work aims to evaluate the antitumoral potential of pomegranate seed protein isolates (PIs), obtained using two different procedures, pressurized liquids (PLE) and high-intensity focused ultrasounds (HIFU), and their hydrolysates on breast cancer cells (HCC1806) and immunodeficient mice (Hsd:Athymic Nude-Foxn1nu). The treatment of HCC1806 cells with increasing concentrations of pomegranate seed PIs and the hydrolysates significantly reduced cell viability. At a concentration of 4 mg/mL (PLE PI), 2 mg/mL (HIFU PI), and 2.4 mg/mL (hydrolysates), all treatments significantly reduced breast cancer cell migration and metalloproteinase 9 (MMP-9) activity (active and pro form), and enhanced cell adhesion. Additionally, a reduction in the proliferation capacity of HCC1806 cells was observed, most likely due to cell cycle arrest and the apoptotic effect of PLE PI and its hydrolysate. In vivo experiments with pomegranate seed hydrolysates confirmed their antitumoral capacity, observing significant reductions in the tumor volume and weight after treating with pomegranate proteins and peptides, as well as in metalloproteinase (MMP) activity and vascular endothelial growth factor (VEGF) expression. In addition to proteins and peptides, the anticancer potential may also be related to the presence of phenolic compounds, especially abundant in the PLE extracts.